Investigation of the physico-chemical characteristics of irrigation water quality at an agricultural site in Pasir Puteh, Kelantan, Malaysia - Anua, Siti Marwanis; Naim, Faridah; Che Azid, Md Khairul Azuan; Jusoh, Juskasmini; Hassan, Noor Artika (Penerbit UTM Press, 2024)
This study was conducted to assess the physico-chemical characteristics of irrigation water quality, focusing on both chemical and physical elements at an agriculture site in Pasir Puteh, Kelantan, Malaysia. Eight sampling points were selected near four different crops namely corn, cucumber, longbean and luffa, with two sampling points located 10 meters apart for each crop. Water samples were analyzed in-situ and ex-situ in evaluating their physico-chemical characteristics including temperature, pH, salinity, conductivity, total dissolved solids (TDS), turbidity, chemical oxygen demand (COD), dissolved oxygen (DO) and biochemical oxygen demand (BOD). The findings revealed that the values of the observed water quality parameters did not exceed the specified standards aligning with the National Water Quality Standards (NWQS) water quality index Class IV – Irrigation. TDS levels at all sampling points were below the NWQS standard for Class I water (<500 mg/L). Although there is no specific turbidity standard for Class IV water, the highest turbidity value was recorded at sampling point 2 (246.50 ± 0.71 NTU). The average COD concentration across all sampling points was 43.63 ± 9.72 mg/L, with a DO value of 3.45 ± 0.55 mg/L, and a mean BOD of 5.80 ± 6.43 mg/L, all falling within Class III NWQS. In conclusion, all measured water quality parameters met the NWQS Class IV irrigation standards, indicating that the water is suitable for irrigation purposes.